Partisipasi Masyarakat dalam Kegiatan Kerja Bakti RT Sebagai Upaya Pembangunan Lingkungan yang Bersih dan Sehat - Ali, Mohammad; Muslikun (PUTRA JAWA PUBLISHER, 2024)
Community service activities are one form of community participation in maintaining and improving the quality of the environment at the Neighborhood Association (RT) level. This study aims to analyze the level of community participation in community service activities and its impact on the development of a clean and healthy environment. The method used is a descriptive approach with data collection through observation, interviews, and surveys to RT residents involved in community service activities. The results showed that active community participation plays a significant role in improving environmental cleanliness and health, such as reduced waste volume, maintained sewer cleanliness, and decreased risk of disease spread. However, there are obstacles in participation that are influenced by internal factors, such as low environmental awareness and busyness of residents, as well as external factors such as lack of supporting facilities. Therefore, strategies to increase community participation are needed, including education on the importance of environmental cleanliness, provision of adequate facilities, and more flexible timing of activities. The conclusion of this study is that community participation in community service is a key element in realizing a clean and healthy RT environment, and efforts to increase participation need to be carried out on an ongoing basis.